Die opstel en evaluering van 'n lees- en spelprogram vir Sesotho-sprekende graad 1-leerders - Koen, Margaretha Paulina (University of the Free State, 2003)
English: Factors such as effective visual and auditive language acquisition are essential for a learner’s success at school, as learning problems are often associated with reading and spelling problems. Research has shown that a learner should receive mother tongue education until grade 7, due to the direct link between a lack of mother tongue education and weak scholastic achievement. A good reading ability is seen as one of the most important scholastic abilities for a learner to be able to develop to his full potential. Reading is an advanced and intricate process, which includes reading abilities such as letter discrimination, sound symbol association, word recognition, phrasing, pronunciation, reading fluency and reading comprehension. Not one single reading method will be effective for all learners and the majority of learners will show progress when different methods are employed. The reading and spelling processes are closely related to each other. The spelling process is a more complex process and is reckoned as the highest form of language ability. In order to spell, the learner depends on the ability to store and recall the words he has read. Spelling problems can develop due to a great variety of internal and/or external factors. There is no effective education method for all learners with spelling problems and spelling should be integrated when the learner is taught other language abilities. A reading and spelling programme have been compiled to stimulate and extend the learners’ interest in both the written and oral use of their mother tongue. A perceptual stimulation programme has also been included into the study to expose the learners to the joy of perceptual stimulation. The reading and spelling programme has been developed in such a way that it can be used in addition to existing education methods. The sampling existed of an experimental group (four subgroups) and a control group. The control group has been chosen in the same way as the experimental group, but the control group did not participate in the programme. The experimental and control groups were paired according to their sex, age and pre-primary school attendance to avoid the variance in the dependent variable, which is caused by interference variables. In this way a more sensitive design and powerful statistical test have been achieved. The Sesotho reading and spelling test has been used in the evaluation of the grade 1 learners’ reading and spelling abilities, as no other standardized measure instrument is available for Sesotho-speaking grade 1 learners. The comparison group did not participate in the programme. The experimental and control groups were paired according to their sex, age and pre-primary school attendance to avoid the variance in the dependent variable, which is caused by interference variables. In this way a more sensitive design and powerful statistical test have been achieved. The Sesotho reading and spelling test has been used in the evaluation of the grade 1 learners’ reading and spelling abilities, as no other standardized measure instrument is available for Sesotho-speaking grade 1 learners. The comparison between the means of the experimental and control groups was verified calculated by using Hotelling’s T-squared (T²) test. The influence of the experimenter has been shown according to the MANOVA-analysis. The findings show that the reading and spelling scores of the experimental group (four subgroups) can be compared and that the one presenter’s group did not achieve significantly better than the other presenter’s group. The results of the statistic calculations show that the programme can successfully improve the reading and spelling ability of the Sesotho-speaking grade 1 learner.

Afrikaans: Doeltreffende visuele en ouditiewe taalbemeestering is noodsaaklike faktore vir skoolsukses, aangesien leerprobleme dikwels met lees- en spelprobleme verband hou. Navorsing het getoon dat leerders verkieslik tot in graad 7 in hulle moedertaal onderrig behoort te word, aangesien daar ‘n regstreekse verband tussen ‘n gebrek aan moedertaalonderrig en swak skolastiese prestasie is. ‘n Goeie leesvaardigheid word dikwels beskou as een van die belangrikste skolastiese vaardighede waaroor ‘n leerder moet beskik om skolasties te vorder. Lees is ‘n gevorderderde en ingewikkelde proses wat leesvaardighede soos letterdiskriminasie, klanksimboolassosiasie, woordherkenning, frasering, uitspraak, leesvlotheid en leesbegrip insluit. Geen enkele leesmetode sal effektief vir alle leerders wees nie en die meerderheid van leerders sal vordering toon wanneer ‘n integrasie van verskillende metodes aangewend word. Daar is ‘n noue verbintenis tussen die lees- en spelproses. Die spelproses is egter ‘n meer gekompliseerde proses en word as die hoogste vorm van taalvaardigheid beskou. Die leerder is afhanklik van die organisasie, stoor en herroeping van gelese woorde, sodat hy kan spel. Spelprobleme kan as gevolg van ‘n groot verskeidenheid interne en/of eksterne faktore ontstaan. Daar is geen effektiewe onderrigmetode vir alle leerders met spelprobleme nie, en spel behoort geïntegreerd en in samehang met ander taalvaardighede aan leerders geleer word. ‘n Lees- en spelprogram is opgestel, sodat leerders se belangstelling in die geskrewe sowel as mondelinge gebruik van hulle moedertaal geprikkel en uitgebrei kan word. ‘n Perseptuele stimuleringsprogram is by die studie ingesluit, sodat alle leerders die blootstelling aan perseptuele stimulering kon geniet. Die lees- en spelprogram is so ontwerp dat dit as aanvullling van bestaande onderrigmetodes kon dien. Die steekproef het uit ‘n eksperimentele en kontrolegroep bestaan. Die kontrolegroep is op dieselfde wyse as die eksperimentele groep gekies, maar eersgenoemde het net nie die program deurloop nie. Die eksperimentele en kontrolegroep is afgepaar ten opsigte van geslag, ouderdom en kleuterskoolbywoning. Die afparingstegniek is gebruik, sodat die variansie in die afhanklike veranderlike wat deur die steuringsveranderlikes veroorsaak kan word, uitgeskakel is. Sodoende is ‘n sensitiewer ontwerp en kragtiger statistiese toets verkry. Die Sesotho lees- en speltoets is tydens die evaluering van die graad 1-leerders se lees- en spelvermoë gebruik, aangesien geen ander gestandaardiseerde meetinstrument vir Sesotho-sprekende graad 1-leerders beskikbaar was nie. Die vergelyking van die gemiddelde afgepaarde tellings vir die eksperimentele en kontrolegroepe is volgens die Hotelling se T²-toets bereken. Die invloed van die proefnemer is volgens die MANOVA-ontleding gedoen. Die bevindinge dui daarop dat die vier subgroepe (eksperimentele groep) se leesen speltellings vergelykbaar is en dat die een aanbieder se groep nie beduidend beter as die ander aanbieder se groep presteer het nie. Die resultate van die statistiese bewerkings dui daarop dat die program suksesvol daarin slaag om die lees- en spelvermoë van die Sesotho-sprekende graad 1-leerders te verbeter.
Keywords: Thesis (Ph.D. (Psychology of Education))--University of the Free State, 2003; Sotho language -- Orthography and spelling; Sotho language -- Study and teaching (Elementary) -- South Africa; Reading (Elementary)